Strategi Berkelanjutan Pengelolaan Limbah Bahan Berbahaya Beracun (B3) di Rumah Sakit X Kota Batam - Sari, Novela; Melisa, Melisa (Universitas Hang Tuah Pekanbaru, 2025)
Ineffective medical waste management can pose serious risks to the environment and public health. With the increasing number of healthcare facilities in Batam City, efficient and safe management of solid medical waste has become a key priority in ensuring environmental sustainability and community well-being. This study aims to identify current practices of solid medical waste management in hospitals and to formulate strategies that align with regulations and local conditions to improve the quality of waste management. The research employed a qualitative design with a case study approach, conducted at one hospital in Batam City. Data were collected through field observations, in-depth interviews, document analysis, and Focus Group Discussions. Data analysis was performed using triangulation techniques, and the results served as the basis for strategy formulation through SWOT analysis. The findings show that most hospitals have complied with the Minister of Environment and Forestry Regulation (PerMenLHK) No. P.56/2015, although technical constraints and limited human resources remain challenges. The attitude of healthcare workers was found to significantly influence waste management practices. The SWOT analysis positioned Hospital X in Quadrant I (aggressive strategy), indicating favorable conditions for improvement. The hospital needs to enhance human resource capacity and implement policies based on the 5R principles (reuse, reduce, recycle, recovery, repair).